Exercise Training Stabilizes RyR2-Dependent Ca2+ Release in Post-infarction Heart Failure - Danielsen, Tore Kristian; Sadredini, Mani; Manotheepan, Ravinea; Aronsen, Jan Magnus; Frisk, Michael; Hansen, Marie Haugsten; Andressen, Kjetil Wessel; Hougen, Karina; Levy, Finn Olav; Louch, William E.; Sejersted, Ole Mathias; Sjaastad, Ivar; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aim Dysfunction of the cardiac ryanodine receptor (RyR2) is an almost ubiquitous finding in animal models of heart failure (HF), and results in abnormal Ca2+ release in cardiomyocytes that contributes to contractile impairment and arrhythmias. We tested whether exercise training (ET), as recommended by current guidelines, had the potential to stabilize RyR2-dependent Ca2+ release in rats with post-myocardial infarction HF. Materials and methods We subjected male Wistar rats to left coronary artery ligation or sham operations. After one week, animals were characterized by echocardiography, and randomized to high-intensity interval ET on treadmills or to sedentary behavior (SED). Running speed was adjusted based on a weekly VO2max test. We repeated echocardiography after five weeks of ET, and harvested left ventricular cardiomyocytes for analysis of RyR2-dependent systolic and spontaneous Ca2+ release. Phosphoproteins were analyzed by Western blotting, and beta-adrenoceptor density was quantified by radioligand binding. Results ET increased VO2max in HF-ET rats to 127 % of HF-SED (P<0.05). This coincided with attenuated spontaneous SR Ca2+ release in left ventricular cardiomyocytes from HF-ET, but also reduced Ca2+ transient amplitude and slowed Ca2+ reuptake during adrenoceptor activation. However, ventricular diameter and fractional shortening were unaffected by ET. Analysis of Ca2+ homeostasis and major proteins involved in regulation of SR Ca2+ release and reuptake, could not explain the attenuated spontaneous SR Ca2+ release or reduced Ca2+ transient amplitude. Importantly, measurements of beta-adrenoceptors showed a normalization of beta1-adrenoceptor density and beta1:beta2-adrenoceptor ratio in HF-ET. Conclusion ET increased aerobic capacity in post-myocardial infarction HF rats, and stabilized RyR2-dependent Ca2+ release. Our data show that these effects of ET can be gained without major alterations in SR Ca2+ regulatory proteins, and indicate that future studies should include upstream parts of the sympathetic signaling pathway.